Is it possible for Village Government Public Services to Be Qualified using Digital-Based Applications? - Ahmad Mustanir; Nurul Ainun Nisa; Razak, Muhammad Rais Rahmat; Kamaruddin Sellang; Jermsittiparsert, Kittisak (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to determine whether using SIBERAS digital technology-based applications can help village governments improve the quality of public services and the factors that influence it. The type of research used is quantitative. Data collection techniquesuse observation and questionnaires. The results showed the quality of public services through the SIBERAS application in Bulovillage, Sidenreng Rappang Regency, Indonesia, on variable X with an unfavorable classification of 56.3%. At the same time, the Yvariable in the excellent classification is 62%. The most influential factor is training. The study's results contribute to developing aresearch roadmap on public services using digital technology-based applications. The limitation of this study is that it only reveals one village in Indonesia, so the research findings cannot thoroughly describe the villages in Indonesia. The following research needsto be carried out in more villages to provide an overview of improving the quality of public services from village governments usingdigital technology-based applications.